Perception of nurses about care and the use of hydrogel in pressure injuries - Cruz, Ronny Anderson de Oliveira (2020)
The study aimed to know the perception of nurses about the use of hydrogels in pressure injuries. This is a research with a qualitative approach conducted in a public hospital in João Pessoa / Paraíba, where the sample consisted of 17 nurses working in the Intensive Care Center, skin committee and red room. Data were collected through an interview using a semi-structured form, and the analysis was performed using the Thematic Content Analysis. It was revealed that there are weaknesses regarding nurses'knowledge regarding pressure injuries and hydrogel application. Noting the need for continuing education in health services, with the aim of alleviating nurses' knowledge limitations regarding the concept, classification and causes of pressure injuries, as well as the use of hydrogel.